2013
DOI: 10.4028/www.scientific.net/amm.393.287
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of Flywheel Hybrid Powertrain to Optimize Energy Consumption in Mechanical Hybrid Motorcycle

Abstract: The creation of internal combustion engine is a significant milestone in power engineering world which simplified high mechanical energy demand jobs like moving vehicle and machinery. Even though the internal combustion engine gives lot of advantages, however, this type of engine is incapable to convert the heat energy from fuel combustion to the mechanical energy efficiently. Small capacity engine e.g. motorcycle engine having the power conversion efficiency between 25-30%. Therefore, alternative power source… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…There are a lot of investigations which have generated models for the components of a hybrid powertrain in the literature (Wenzhong Gao et al, 2007;Wishart, 2008;Liukkonen, 2012;Feng and Huang, 2012;Molla, 2010;Abdul Manaf et al, 2013;Diego-Ayala, 2007). In this paper, the method using look-up tables are presented for modeling of three hybrid powertrains.…”
Section: Powertrain Modellingmentioning
confidence: 98%
“…There are a lot of investigations which have generated models for the components of a hybrid powertrain in the literature (Wenzhong Gao et al, 2007;Wishart, 2008;Liukkonen, 2012;Feng and Huang, 2012;Molla, 2010;Abdul Manaf et al, 2013;Diego-Ayala, 2007). In this paper, the method using look-up tables are presented for modeling of three hybrid powertrains.…”
Section: Powertrain Modellingmentioning
confidence: 98%
“…They concluded that the payback for additional mechanical hybrid components would be achieved after approximately 50,000 km. Manaf et al 18 presented simulations of a motorcycle equipped with a flywheel for kinetic energy storage and recuperation. They showed that the inclusion of the flywheel in the drivetrain enabled a 36% reduction in fuel consumption on their simplified representative drive cycle.…”
Section: Introductionmentioning
confidence: 99%
“…In performance aspect, the major drawback of flywheel hybrid is in the recharging and storing capability. It only can be charge using regenerative braking which exist during deceleration phase of driving cycle [1]. Although the engine can be used to recharge it, but there is no point because the main purpose of hybrid is to reduce the operation time of the engine.…”
Section: Introductionmentioning
confidence: 99%